Effect of different organic acid additives on the fermentation quality and bacterial community of paper mulberry (Broussonetia papyrifera) silage - Li, Mengxin; Yu, Qiang; Xu, Jinyi; Sun, Hong; Cheng, Qiming; Xie, Yixiao; Wang, Chunmei; Li, Ping; Chen, Chao; Zheng, Yulong (Frontiers in Microbiology, 2022)
To investigate the effects of different organic acid additives and their concentrations on the fermentation quality and bacterial community of paper mulberry silage, paper mulberry was left untreated (control) or was treated with ethylenediaminetetraacetic acid (EDTA), propionic acid (PA) or citric acid (CA), the amount of each additive was 2 g.kg-1 FM, 5 g.kg-1 FM and g.kg-1 FM. All groups were ensiled for 3, 7, 15, 30 and 60 days. Compared to the control, adding EDTA reduced protein breakdown, preserved more water-soluble carbohydrates of the silages (WSCs, 24.74 g.kg-1 DM), and high concentrations of EDTA inhibited the activity of undesirable microorganisms. Adding PA increased the abundance of Lactiplantibacillus and decreased the abundance of Enterococcus, and it caused a rapid decrease in the pH of the silage at an early stage (from 6.50 to 5.31) while altering the microbiota, and low concentrations of PA resulted in high LA (66.22 g.kg-1 DM) concentration and low PA (9.92 g.kg-1 DM) concentration at 60 days of ensiling. Different concentrations of additives altered the microbial community of paper mulberry to different degrees. High concentrations of PA and CA can increase the abundance of Lactiplantibacillus. High concentrations of CA resulted in a rapid decrease in silage pH at an early stage and higher WSC concentration. These results suggest that EDTA, PA and CA can be used as additives to improve the quality of paper mulberry silage.